Asparagus racemosus: A newly proposed natural preservative for improved lipid oxidative stability and storage quality of meat products. Issue 5 (11th September 2017) - Noor, Sabahu; Bhat, Z.F.; Kumar, Sunil; Kousar, Insha
Abstract : Purpose: This paper aims to explore the possibility of utilization of Asparagus racemosus as a novel natural preservative in meat products. Design/methodology/approach: Chevon sausages were used as a study model and prepared by incorporating different levels of A. racemosus, namely, T1 (0.25 per cent), T2 (0.50 per cent) and T3 (0.75 per cent) and were vacuum packaged and assessed for various lipid oxidative stability and storage quality parameters under refrigerated (4  ±  1°C) conditions. Findings: Significantly ( p < 0.05) lower thiobarbituric acid reacting substances (mg malonaldehyde/kg) values were observed for the products containing A. racemosus in comparison to control indicating a significant effect on the lipid oxidative stability. The products containing A. racemosus also showed significantly ( p < 0.05) lower values for various microbiological characteristics like total plate count (log cfu/g), psychrophilic count (log cfu/g), yeast and mould count (log cfu/g), anaerobic count (log cfu/g) and free fatty acid (% oleic acid) values indicating the antimicrobial and antifungal properties of A. racemosus . No significant ( p > 0.05) effect was observed on the cooking yield and moisture content of the products. Significantly ( p < 0.05) higher scores were observed for various sensory parameters of the products containing A. racemosus during the entire period of storage. Originality/value: A. racemosus successfully improved the lipid oxidative stability and storage quality of the model meat product without compromising the sensorial characteristics and has a great potential as a novel natural preservative in muscle foods.